Geochemical bias in drill cutting samples versus drill core samples returned from the Reykjanes Geothermal System, Iceland. (July 2016) - Fowler, Andrew P.G.; Zierenberg, Robert A.
Highlights: Drill-cutting samples are biased towards preservation of least altered primary igneous minerals and more resistant alteration minerals, and preferential loss of finer-grained and less resistant minerals. Mixing of drill cutting samples can be severe at great depth, and obscures details of the primary lithology and extent of alteration. Drill cutting samples reflect contamination by metal alloys used in drill bits and drill collars, including Cu, Ni, Cr and Ta. Abstract: The wholerock major and trace element composition of drill cutting samples are compared to drill core samples from adjacent depths in the seawater recharged Reykjanes geothermal system in Iceland. The first appearance of alteration minerals and lithologies in drill cutting samples is a useful tool for interpreting broad subsurface characteristics. However, use of drill cutting samples for determining igneous affinity and elemental exchanges during hydrothermal alteration is problematic. Samples recovered from immediately above and below the cored intervals in wells RN-17B and RN-30 demonstrate that drill-cutting samples are biased towards preservation of least altered primary igneous minerals and more resistant alteration minerals, including albite, quartz, and epidote, with preferential loss of finer-grained and less resistant minerals including chlorite and actinolite. This selective recovery obscures elemental exchanges resulting from hydrothermal alteration processes. For some elements, compositional variations (enrichments and depletions) measured from 9.5 m of core exceeds that observed in ∼3000 m of cutting analyses. Concentration ratios of hydrothermally immobile elements including Zr, Nb, V, Y, HREE, Hf, Ta and Th in deep (>2245 m) spot drill core samples record bimodal, trace element-enriched and trace element-depleted precursor compositions similar to subaerial Reykjanes Peninsula basalts. The same elements in nearly 3000 m of drill cutting samples from well RN-17 overwhelmingly reflect the more common trace element-enriched igneous precursor, demonstrating that mixing of drill cutting samples obscures details of their igneous affinity. A new and different drill rig was used to deepen well RN-17 below 2266 m in a sidetrack hole (RN-17ST), which resulted in a change in drilling conditions, accompanied with an increased well deviation angle from ∼0° to ∼4°. Wholerock geochemical results for drill cutting samples from RN-17ST are homogenous for virtually every element; suggesting the change in drilling conditions resulted in extreme mixing of the drill cuttings. Anomalously high concentrations of Cu, Ni, Cr and Ta in some drill cutting samples likely reflects contamination of drill cutting samples by metal alloys used in drill bits and drill collars or more resistant spinel and sulfide phases.